A Correlational Study between Metacognitive Reading Strategies and Reading Motivation Toward Reading Comprehension in ESP Students - Karlina Karadila Yustisia (Graduate Program, University of Islam Malang, 2020)
The comprehension of reading become daunting for ESP students. The purpose of this research is to establish whether there is a significant relationship between student use of metacognitive reading strategies and reading comprehension; motivation for reading English text and reading comprehension; metacognitive reading strategies and motivation for reading toward reading comprehension of ESP Students at the second semester of Economics and Business department. The findings of this study showed a strong association between student use of metacognitive reading strategies and reading comprehension. Accordingly, there is also a strong relationship between reading motivation and reading comprehension. Nevertheless, there is a significant correlation between metacognitive reading strategies and reading motivation for reading comprehension.